The Effect of Filter Media Grain Size on the Headloss and Backwash Duration at PT PAM Lyonnaise Jaya (PALYJA) - Putri, Septiani Eka; Zahra, Nurulbaiti Listyendah; Sarwono, Ariyanti; Nastiti, Almira Davina; Sekarsari, Dinda (Journal of Sustainable Infrastructure, 2024)
This research is about the effect of filter media grain size on the headloss and backwash duration of rapid sand filter unit. The purpose of this study is to analyze the effect of filter media grain size on headloss and backwash duration. In this research, filter media with 3 different sizes are used, which are assessed based on the effective size (ES) and uniformity coefficient (UC) parameters. Data collection consists of sieve analysis of media filter, headloss test, turbidity test, and TSS test. The Headloss test is carried out on a laboratory scale using a prototype filter unit. Sieve analysis of media filter, turbidity test, and TSS test of backwash water are carried out at IPA 2 PT PAM Lyonnaise Jaya. The results show that each value of headloss for large filter media (ES = 1.29 mm; UC = 1.40), small filter media (ES = 0.87 mm; UC = 1.51), and mixed filter media (ES = 0.89 mm; UC = 1.49) are 4 cm, 5.5 cm, and 4.6 cm. The optimum backwash duration on large filter media, small filter media, and mixed filter media are 15 minutes, 13 minutes, and 14 minutes.